2011
DOI: 10.1167/iovs.10-6390
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of In Vivo Confocal Microscopic Findings between epi-LASIK Procedures with Different Management of the Epithelial Flaps

Abstract: On- and off-flap epi-LASIK showed comparable clinical outcomes after surgery. Off-flap epi-LASIK had more rapid re-epithelialization and normalization of epithelial morphology than did on-flap epi-LASIK, when observed by in vivo confocal microscopy. (ClinicalTrials.gov number, NCT00491439.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
1
10
0
1
Order By: Relevance
“…Six RCTs and 3 comparative studies published between 2008 and 2011 met the inclusion criteria [7,8,9,13,14,15,16,17,18]. A total of 489 patients (958 eyes) underwent off-flap epi-LASIK and on-flap epi-LASIK.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six RCTs and 3 comparative studies published between 2008 and 2011 met the inclusion criteria [7,8,9,13,14,15,16,17,18]. A total of 489 patients (958 eyes) underwent off-flap epi-LASIK and on-flap epi-LASIK.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 489 patients (958 eyes) underwent off-flap epi-LASIK and on-flap epi-LASIK. Patients’ mean age ranged from 20.25 to 33 years and the mean preoperative manifest spherical equivalent (MSE) ranged from –3.49 D to –9.14 D; 0.02% mitomycin C (MMC) was used for 15–120 s in 6 studies [9,13,14,16,17,18]. Each study revealed that there were no significant differences in preoperative demographic features and other factors that may have influenced surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding suggested that the centripetal migration of remaining peripheral corneal epithelial cells occurred in order to quickly cover the denuded wound surface. [9][10][11] Cho et al 12 also found that in rabbit corneas after epithelial debridement, the morphology of initially healing superficial cells were elliptical and large. Changes from single to multiple layers of corneal epithelia implied that epithelial differentiation occurred.…”
Section: Discussionmentioning
confidence: 96%
“…To facilitate following analysis, the cells superficial to BECs were defined as corneal apical surface cells (ASCs) in this study, just as described in previous reports. 9,10 ICs were characterized by round hyperreflective nucleus under LSCM with an average diameter of o10 μm. DCs appeared to be hyperreflective corpuscular particles with dendritic processes, scattering among limbus or gathering in group.…”
Section: Image Analysismentioning
confidence: 99%